2023
DOI: 10.3390/antibiotics12061003
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Empirical Antimicrobial Therapy in Enterobacterales Bloodstream Infection Using the Extended-Spectrum Beta-Lactamase Prediction Score

Brian J. Haimerl,
Rodrigo Encinas,
Julie Ann Justo
et al.

Abstract: Clinical tools for the prediction of antimicrobial resistance have been derived and validated without examination of their implementation in clinical practice. This study examined the impact of utilization of the extended-spectrum beta-lactamase (ESBL) prediction score on the time to initiation of appropriate antimicrobial therapy for bloodstream infection (BSI). The quasi-experimental cohort study included hospitalized adults with BSI due to ceftriaxone-resistant (CRO-R) Enterobacterales at three community ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…In one systematic review examining scoring tools for predicting ESBL presence and carbapenem resistance in Enterobacterales bloodstream infections, subsequent external validation studies reported a median sensitivity and specificity of 32% and 90% for ESBL prediction, which were lower than that of their original studies (55% and 94%, respectively) ( 12 ). In another study at several community hospitals, the implementation of an ESBL diagnostic scoring tool in Enterobacterales bloodstream infections led to a significant decrease in mean time to appropriate antibiotic administration (78 hours before to 46 hours after implementation) ( 13 ). Altogether, these findings underscore the potential clinical relevance of these tools, particularly for NPV among low incidence settings, and the necessity of local validation of diagnostic scoring tools to ensure effective implementation.…”
Section: Discussionmentioning
confidence: 99%
“…In one systematic review examining scoring tools for predicting ESBL presence and carbapenem resistance in Enterobacterales bloodstream infections, subsequent external validation studies reported a median sensitivity and specificity of 32% and 90% for ESBL prediction, which were lower than that of their original studies (55% and 94%, respectively) ( 12 ). In another study at several community hospitals, the implementation of an ESBL diagnostic scoring tool in Enterobacterales bloodstream infections led to a significant decrease in mean time to appropriate antibiotic administration (78 hours before to 46 hours after implementation) ( 13 ). Altogether, these findings underscore the potential clinical relevance of these tools, particularly for NPV among low incidence settings, and the necessity of local validation of diagnostic scoring tools to ensure effective implementation.…”
Section: Discussionmentioning
confidence: 99%
“…As noted, in the two studies evaluating clinical utility, only the hypothetical undertreatment, overtreatment, and carbapenem use per 1000 patient days was evaluated. However, the collaborators of the Augustine study recently published a separate subsequent study evaluating the implementation of their risk prediction scoring on patient management [ 28 ]. For their implementation, they made the prediction score and algorithm available in print, on their internal website for providers, and through a mobile app.…”
Section: Discussionmentioning
confidence: 99%